The Application Of Tblt In College Oral English Teaching - Pang, Xiao (Journal of Theory and Practice of Social Science, 2023)
Task-based teaching method is a new teaching method in the current new curriculum reform education, which is widely used in different stages and different subjects. It comes from constructivism, which is generalized and applied at the last practical end. Constructivism of TBLT is mainly reflected in classroom teaching. Through in-depth analysis of this theoretical concept, it is clearly recognized that constructivism is the theoretical basis for learning and knowledge formation, while constructivism means that students can effectively learn and accumulate different knowledge through textbooks or other channels [1]. Different from the traditional teaching mode, students gradually form the mutual help between teachers and students by passive learning, effectively cultivate students' subjective initiative, improve their interest in learning, deeply tap students' English potential, and quickly form a good habit of independent learning. In-depth analysis shows that TBLT application in language classroom teaching no longer follows the traditional teaching principles and gradually replaces the infusing teaching mode.